Jawabanmu

2014-03-24T20:40:54+07:00
 \frac{cos(90- \alpha )}{sin(90- \alpha )}
 \frac{cos90 cos \alpha + sin90 sin \alpha }{sin90 cos \alpha  - cos90 sin \alpha }
= \frac{0(cos \alpha ) + 1(sin \alpha )}{1(cos \alpha ) - 0(sin \alpha )}
 \frac{sin \alpha }{cos \alpha }
= tanα

rumus:
cos(a-b) = cosa cosb + sina sinb
sin (a-b) = sina cosb - cosa sinb
sin 90 = 1
cos 90 = 0
kenapa bisa begitu kak?
pake rumus yang udah aku tulis diatas
udah aku edit, cos90 dimasukkin 0, sin90 dimasukkin 1. udh paham blm?